A review of carboxymethyl cellulose composite-based hydrogels in drug delivery applications - Yash Gupta; Mohammad Sohail Khan; Mansi Bansal; Manish Kumar Singh; K Pragatheesh; Archana Thakur (Results in Chemistry, 2024)
The use of naturally occurring biopolymers in the drug delivery applications have attracted significant attention due to their biocompatibility, biodegradability, and non-toxicity. Over the years, carboxymethyl cellulose, a natural polymer has emerged as a good candidate due to its molecular-binding and gel-forming properties. This review study comprehensively explores the CMC composites-based hydrogels as efficient drug delivery systems. Various hydrogels synthesized using CMC with additives such as tamarind gum, xanthun gum, gelatin, graphene oxide, polyacrylamide, chitosan etc. are discussed in terms of drug delivery in this study. Specific examples of drugs involve acyclovir, 5-fluorouracil, doxorubicin, and curcumin. The novelty of this study lies in its comprehensive evaluation of carboxymethyl cellulose composite-based hydrogels, highlighting their potential to enhance drug delivery efficacy, pH sensitive, targeted and comprehensive drug release, offering a biocompatible, biodegradable, non-toxic alternative to synthetic polymers for drug delivery applications.